Progress in Semitransparent Organic Solar Cells. Issue 5 (26th March 2021) - Duan, Leiping; Hoex, Bram; Uddin, Ashraf
Abstract : Opaque and semitransparent organic solar cells (ST‐OSCs) have made tremendous progress in recent years. Efficiencies over 18% and 13% have been demonstrated for opaque ST‐OSCs, respectively. OSCs do not contain unfavorable elements such as lead, which makes them available for broader potential applications when compared with other lead‐contained thin‐film solar cells. There has also been tremendous progress in the ST‐OSCs, which makes them extremely appealing for promising emerging applications such as building‐integrated photovoltaics. Herein, a progress review in the field is presented for helping the researchers better understand ST‐OSCs and further realize their potentials. Recent strategies in ST‐OSCs based on three perspectives are summarized, including electrode engineering, active layer engineering, and device engineering. A wide range of applications where ST‐OSCs can be used is discussed and challenges for future developments of ST‐OSCs are pointed out. Finally, the outlook for promising future research directions is presented. Abstract : 1) Recent progress in semitransparent organic solar cells (ST‐OSCs) is summarized, 2) multifunctional applications of ST‐OSCs are discussed, 3) challenges for future developments of ST‐OSCs are proposed, and 4) outlooks of promising future research directions for ST‐OSCs are presented.